Inhibition of Phosphodiesterase 3A by Cilostazol Dampens Proinflammatory Platelet Functions - Daniëlle M. Coenen; Alexandra C. A. Heinzmann; Silvia Oggero; Hugo J. Albers; Magdolna Nagy; Perrine Hagué; Marijke J. E. Kuijpers; Jean-Marie Vanderwinden; Andries D. van der Meer; Mauro Perretti; Rory R. Koenen; Judith M. E. M. Cosemans (Cells, 2021)
Objective: platelets possess not only haemostatic but also inflammatory properties, which combined are thought to play a detrimental role in thromboinflammatory diseases such as acute coronary syndromes and stroke. Phosphodiesterase (PDE) 3 and -5 inhibitors have demonstrated efficacy in secondary prevention of arterial thrombosis, partially mediated by their antiplatelet action. Yet it is unclear whether such inhibitors also affect platelets’ inflammatory functions. Here, we aimed to examine the effect of the PDE3A inhibitor cilostazol and the PDE5 inhibitor tadalafil on platelet function in various aspects of thromboinflammation. Approach and results: cilostazol, but not tadalafil, delayed ex vivo platelet-dependent fibrin formation under whole blood flow over type I collagen at 1000 s−1. Similar results were obtained with blood from Pde3a deficient mice, indicating that cilostazol effects are mediated via PDE3A. Interestingly, cilostazol specifically reduced the release of phosphatidylserine-positive extracellular vesicles (EVs) from human platelets while not affecting total EV release. Both cilostazol and tadalafil reduced the interaction of human platelets with inflamed endothelium under arterial flow and the release of the chemokines CCL5 and CXCL4 from platelets. Moreover, cilostazol, but not tadalafil, reduced monocyte recruitment and platelet-monocyte interaction in vitro. Conclusions: this study demonstrated yet unrecognised roles for platelet PDE3A and platelet PDE5 in platelet procoagulant and proinflammatory responses.